Tannin extracted from Penthorum chinense Pursh, a potential drug with antimicrobial and antibiofilm effects against methicillin-sensitive Staphylococcus aureus and methicillin-resistant Staphylococcus aureus - Qin, Junyuan; Yu, Lei; Peng, Fu; Ye, Xin; Li, Gangmin; Sun, Chen; Cheng, Fang; Peng, Cheng; Xie, Xiaofang (Frontiers in Microbiology, 2023)
Staphylococcus aureus is an opportunistic pathogen. Due to the widespread use and abuse of antibiotics, various drug-resistant strains of S. aureus have emerged, with methicillin-resistant Staphylococcus aureus (MRSA) being the most prevalent. Bacterial biofilm is a significant contributor to bacterial infection and drug resistance. Consequently, bacterial biofilm formation has emerged as a therapeutic strategy. In this study, the chemical constituents, antimicrobial and antibiofilm properties of tannins isolated from Penthorum chinense Pursh (TPCP) were investigated. In vitro, TPCP exhibited antimicrobial properties. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) for methicillin-sensitive Staphylococcus aureus (MSSA) and MRSA were 156.25 and 312.5 μg/mL, and 312.5 and 625 μg/mL, respectively. According to the growth curves, TPCP significantly inhibited the growth of MSSA and MRSA. The results of the crystal violet biofilm assay in conjunction with confocal laser scanning and scanning electron microscopy demonstrated that TPCP destroyed preformed MSSA and MRSA biofilms. TPCP significantly decreased the secretion of exopolysaccharides and extracellular DNA. Subsequently, the mechanism was investigated using RT-PCR. Examining the expression of icaA, cidA, sigB, agrA, and sarA genes in MRSA, we discovered that TPCP inhibited biofilm formation by affecting the quorum-sensing system in bacteria. Our study demonstrates that TPCP exerts antibacterial effects by disrupting the formation of bacterial biofilms, suggesting that TPCP has clinical potential as a novel antibacterial agent for the prevention and treatment of MSSA and MRSA infections.